Meningkatkan Motivasi Belajar Al-Qur’an Surat At-Tin Siswa Kelas VII SMP N 1 Sungai Beremas Melalui Model Cooperatif Learning - Ainun Syharo Lubis; Ahmad Rajali (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to increase the focus of students in learning Islamic Religious Education (PAI) by increasing the motivation to learn the Al-Qur'an Surah At-Tin in class VII students of SMPN 1 Sungai Beremas through the cooperative learning model during the 2023/2024 academic year. By using a classroom action research (CAR) approach, this study was conducted in two cycles that included planning, action, observation, and reflection. The learning outcomes of class VII students of SMP N 1 Sungai Beremas increased from cycle I to cycle II, as seen from the level of student completion which increased by 42.86% and students who did not complete also decreased by 42.86%. The cooperative learning model has proven effective in motivating learning the Al-Qur'an Surah At-Tin in class VII students of SMP N 1 Sungai Beremas.